Bayanihan and Belonging : Filipinos and Religion in Canada - Marshall, Alison, 1965- (Book collections on Project MUSE., 2018)
Drawing on archival and ethnographic research in Canada and the Philippines from 1880 to 2017, Bayanihan and Belonging aims to understand the role of religion within present-day Filipino Canadian communities.